Teoria magistral. Równowaga i stabilność optymalnych procesów wzrostu w modelach dynamiki ekonomicznej = Turnpike theory. Equilibrium and stability of optimal growth processes in dynamic economic models - Panek, Emil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the second half of the 1950s, Paul A. Samuelson formulated a hypothesis concerning the long-term convergence of optimal growth paths to a certain "benchmark" path along which an economy achieves its maximum, steady growth rate. Samuelson compared this benchmark path - representing the economy in a kind of dynamic equilibrium (growth equilibrium) - to a highway in road transportation. By identifying towns with economic states, the highway rule can be stated as follows: Starting from historically shaped initial conditions, a properly (optimally) functioning economy should reach the benchmark growth path (or its close vicinity) as quickly as possible, then continue to grow while remaining on or near this path, and eventually - toward the end of the considered time horizon - diverge from it if necessary to reach the desired final state.
Keywords: model matematyczny stacjonarnej i niestacjonarnej gospodarki; równowaga von Neumanna; magistrala produkcyjna; stabilność magistralna optymalnych procesów wzrostu; mathematical model of stationary and non-stationary economies; von Neumann equilibrium; production turnpike; turnpike stability of optimal growth processes